Pengaruh Tambahan Penghasilan Pegawai (TPP) Terhadap Kinerja Pegawai Dinas Kependudukan Dan Pencatatan Sipil Pemerintah Provinsi Sulawesi Selatan - Irma Sumiaty; Andi Hendra Syam; Amiruddin Amiruddin (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research aims to identify the influence of providing additional employee income on the performance of employees of the Population and Civil Registration Service of the South Sulawesi Provincial Government. The sample in this study were all employees who worked at the Population and Civil Registration Service of the South Sulawesi Provincial Government. The data in this research was collected using a survey research method, namely by distributing questionnaires directly to employees who work at the Population and Civil Registration Service of the South Sulawesi Provincial Government. The research results will be analyzed using multiple regression analysis. The results of this research show that additional employee income has an effect on the performance of employees at the Population and Civil Registration Service of the South Sulawesi Provincial Government.